Pengembangan Aplikasi Permainan Edukasi Untuk Pengenalan Warna Dasar Menggunakan Markerless Augmented Reality - Vio Cesar Melano Yonanta; Tri Afirianto; Wibisono Sukmo Wardhono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Early childhood needs education and coaching to help their growth and development. One of the coaching efforts for children is to introduce basic colors to them. The way for children to improve their cognitive abilities so they can recognize basic colors, and get a pleasant visual experience in recognizing basic colors is a challenge for teachers and parents. Therefore, an educational game or game application is made that utilizes marker-less augmented reality technology to provide a pleasant experience such as watching virtual objects join the real world to children and improve children's cognitive abilities in recognizing basic colors by giving instructions through augmented reality technology. The method used in this study is the Game Development Life Cycle (GDLC). Based on the research conducted, it was concluded that the gameplay of the educational game developed can improve children's visual experience in recognizing basic colors and children's cognitive abilities in recognizing basic colors can be increased by the influence of educational games that have been developed.